FOOD DISCOURSE IN MODERN WORLD LITERATURE - Shahlo Oblokulova (Western European Studies, 2024)
In modern world literature, food discourse is studied as a scientific science that talks about certain qualities of food, its existence, methods of its description and forms of supply. This discourse is formed on the basis of the knowledge of the physical structural structure of food, the theory, the changes that occur during the preparation, preparation and consumption of food, literary principles and necessary requirements indicated by writers and teachers.
Keywords: principles; necessary; requirements